Aportes a la interpretación de sitios arqueológicos con iconografías secuenciales, el caso de la cronofotografía en huaca de la luna, moche, Perú - López Estupiñán, Laura (2016)
This research aims to contribute to the interpretation of sequential iconography and the sites where they are. Here, the application of archaeological and photometric methods analytical techniques such as linking chronophotography and morphometry, allow us to understand the images of facades, walls and ceramics as dynamic images depicting movement, beyond simple scenes. The study includes the iconographic analysis of the mural architecture Eier 3 (E3), north frontis and replication of methodological model vessels bell-shaped ceramics called vases and Aia-paec Building D platform I, which were excavated and preserved by the Temples of the Sun and the Moon Archaeological Project (PAHSL). As a result we obtained 570 image sequences, 38 drawings and 13 digitized animations confirming the sequentiality between images.